ANALYSIS OF THE DETERMINANTS OF JOB SATISFACTION AND EMPLOYEE PERFORMANCE - Siswadi, Yudi; Jufrizen, Jufrizen; Arif, Muhammad (SULTANIST: Jurnal Manajemen dan Keuangan, 2025)
This study aims to analyse the effect of Person-Organisation Fit and Leadership on Employee Performance through Job Satisfaction as an intervening variable in employees of PT. Socfindo Medan. The population in this study consisted of all permanent employees of PT Socfindo Medan, totalling 217 individuals. The sample in this study consisted of 68 people, determined using the Slovin formula. The data collection technique uses a questionnaire. Data analysis using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The research results show that Person Organization Fit has a positive and significant effect on Employee Performance, Leadership has a positive and significant effect on Employee Performance, Person Organization Fit has no significant effect on Job Satisfaction, Leadership has a positive and significant effect on Job Satisfaction, Job Satisfaction has a positive and significant effect on Employee Performance, Person Organization Fit has no significant effect on Employee Performance through Job Satisfaction as an intervening variable, and Leadership has a positive and significant effect on Employee Performance through Job Satisfaction as an intervening variable.